Deep and intermediate water mass history of the Western Indian Ocean - Maxwell, Jamie Lyon (The University of Edinburgh, 2019)
This research focuses on reconstructing the history of various oceanic conditions, ranging from surface to deep layers, in the Western Indian Ocean over the last glacial cycle. A new data set is presented, composed of various palaeoceanographic proxies from marine sediment cores 64PE304-8 (752m), 64PE303-16 (1350m) and 64PE303- 15 (1985m) retrieved along a depth transect during the “Tropical Temperature History During Paleogene Global Warming Events” (GLOW) ? and “Indian – Atlantic Exchange” (INATEX) ? expeditions of the research vessel Pelagia. Interpretation of this new data, forming a vertical transect of geochemical proxies of terrigenous hydrological change and foraminiferal stable isotope records anchored in robust radiocarbon based age models, provides a significant contribution to an area of poor data coverage in the western Indian Ocean. Geochemical records of eastern African hydrological change provide a record of monsoon driven rainfall changes. We show that orbitally driven cycles in the log (Ti/Ca) series are a direct response to regional equatorial insolation. We notice that the structure of the precessionally driven cycles shows no similarity with the widely cited monsoonal influenced Chinese cave speleothem records (??). The offshore Tanzanian records show a remarkable resemblance with the newly published Borneo cave speleothem record (?), both likely driven by near regional equatorial insolation patterns. Millennial scale events are strongly manifest in the log(Ti/Ca) series in intervals where sedimentation rates are relatively high, punctuating the longer-term precessionally driven cycles. The log(Ti/Ca) series show a number of distinct dry events, which occurred synchronously with the northern hemisphere cold Heinrich events. The data show a strong coupling between changes in monsoon rainfall offshore Tanzania and the northern hemisphere Heinrich cold events, likely mediated by the average position of the intertropical convergence zone. The stable isotope data helps our understanding of variability of surface, intermediate and deep ocean circulation in the western Indian Ocean on the millennial time-scale. The depth transect approach allows us to investigate time offsets between the individual stable isotope records of the surface, intermediate and deep waters during the late glacial-Holocene cycle. The time off sets are useful indicators of connections between changes in western Indian Ocean water masses and climate change in the high latitudes. Our new data highlights significant differences across the water column in the timing of deglaciation. We can robustly report that the intermediate depth ocean in the region of our cores was the first to record an oxygen isotope signal of the deglaciation. The rate of change records calculated further show the offsets and elucidate the apparent relationship between our surface records and Greenland in terms of timing of change. The records presented here are also placed in a broader Indian Ocean/Arabian sea context to asses to role of the intermediate depths of the Indian Ocean in millennial scale change, particularly during Heinrich events. Using the combined insights provided by the new δ18O and δ13C records, the new transect of records highlights changes in the nature of intermediate depth Indian Ocean circulation changes over the last 40kyr. This contributes to the discussion of the origin of the oxygenation pulses in the Arabian Sea, that either reflect local changes in intermediate water properties, or indeed bear evidence of a larger, Indian Ocean wide expansion of glacial Antarctic Intermediate water. The new data are combined with published data to assess modes of ocean circulation in the Indian Ocean. This helps to elucidate the role played by this part of the global ocean system in the millennial-scale climate shifts - including the bipolar seesaw phenomenon - that occurred during this time period. In particular, two valuable insights into past changes in ocean circulation in the western Indian Ocean are presented, with important implications for our understanding of the role of ocean circulation in millennial scale and deglacial climate shifts. First, our new data supports the notion of expanded glacial AAIW at intermediate depths within the Indian Ocean during Heinrich events. Second, we see evidence of a deglacial reorganistaion of the ventilation pattern in the region across the deglaciation. This involves an chemically aged watermass reaching the upper 1000m of the western Indian Ocean via the Indonesian Through-flow and the SEC.
Keywords: Western Indian Ocean; marine sediment cores; Paleogene Global Warming; foraminiferal stable isotope; terrigenous hydrological change; equatorial insolation patterns; Heinrich events; stable isotope data; ocean circulation changes; deglacial reorganisation; ventilation pattern